The influence of cage farming on infection of the corvine fish Plagioscion squamosissimus (Perciformes: Sciaenidae) with metacercariae of Austrodiplostomum compactum (Digenea: Diplostomidae) from the Chavantes reservoir, São Paulo State, Brazil. Issue 3 (September 2014) - Ramos, I.P.; Franceschini, L.; Zica, É.O.P.; Carvalho, E.D.; Silva, R.J.
Abstract The development of cage fish farms has been associated with an increase in parasitic diseases. Organic matter resulting from feed waste and faeces attracts animals such as birds and invertebrates that can act as hosts for parasites. The aim of this study was to evaluate the influence of cage farming on Austrodiplostomum compactum metacercariae infections of Plagioscion squamosissimus collected close to a cage farm in the Chavantes reservoir (Paranapanema River). Thirty-seven fish were collected in an area close to cages (CF), and 28 in an area not influenced by cages (CT). All specimens were weighed, measured and the eyes removed for morphological analyses of metacercariae. The prevalence, mean intensity of infection, mean abundance and condition factor were calculated. The prevalence (CF = 86.4%, CT = 57.1%), mean infection intensity (CF = 20.31 ± 1.13, CT = 4.29 ± 7.14) and mean abundance (CF = 17.70 ± 6.27, CT = 2.35 ± 0.77) were higher in the CF (P< 0.05) group. There were no significant correlations (P> 0.05) between the mean abundance and standard length or the total weight and condition factor in either group (P> 0.05). Fish farms may interfere with the life cycle of A. compactum, leading to more infections with P. squamosissimus. This could be due to an increase in the number of host animals that are attracted by the availability of food resources derived from fish farms.